Geochemistry of the Bottom Sediments of Lake Peyungda, Tunguska Nature Reserve, and Paleoclimatic Reconstructions of the Arctic Territories of Eastern Siberia - Novikov, V. S.; Darin, A. V.; Babich, V. V.; Darin, F. A.; Rogozin, D. Yu (Geochemistry international, 2024)
Lake Peyungda contains annually layered bottom sediments (varves), which make it possible to build a reliable age model for the entire depth of the core. An age model was refined over the last century based on the presence of a layer of anomalous thickness associated with the fall of the Tunguska cosmic body (TCB) in June 1908. The results of scanning µXRF-SI (elemental analysis along core depth) were used for comparison with regional average annual weather observation data over the time span of 1895–2000 to create a transfer function: average annual temperature as a function of the elemental composition of the dated layer of bottom sediment. Approximation of the obtained function to the depth of core sampling made it possible to reconstruct changes in regional temperature over the time interval of the last millennium with an annual time resolution. Comparison of the obtained reconstruction with literature data on reconstructions for the Arctic region over the past 1000 years shows the presence of general trends and extremes, which confirms the reliability of the obtained results.